2019
DOI: 10.4103/ijpsym.ijpsym_188_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical and Coercion Characteristics of Patients who Abscond during Inpatient Care from Psychiatric Hospital

Abstract: Background:Patients absconding from psychiatric hospitals pose a serious concern for the safety of patients and public alike. Absconding is associated with an increased risk of suicide, self-harm, homicide, and becoming “missing” from society. There are only scarce data on profile and outcome of the absconding patients in India.Aims:To study the prevalence and describe the clinical and coercion characteristics of patients who abscond during inpatient care from an open ward.Methodology:“Absconding” was defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
12
1
Order By: Relevance
“…Further research should focus on this event with a longer period of observation and should include This finding is also supported by previous descriptive and case-control studies, which found psychotic illness to be a common factor predicting absconding events. 5,12,22,24,31,37 A few studies have also found increased rates of affective illness, substance use, and personality disorders. 10,38,39 A significantly higher proportion of patients who absconded had irritable affect both at the time of admission and around the time of absconding.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Further research should focus on this event with a longer period of observation and should include This finding is also supported by previous descriptive and case-control studies, which found psychotic illness to be a common factor predicting absconding events. 5,12,22,24,31,37 A few studies have also found increased rates of affective illness, substance use, and personality disorders. 10,38,39 A significantly higher proportion of patients who absconded had irritable affect both at the time of admission and around the time of absconding.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study from a psychiatric hospital in India also found a higher prevalence of absconding among patients who had an absent insight. 24 About 10% of cases had a history of prior absconding from the hospital in the previous admissions. This proportion is less than what was found by Meehan et al, 40 who found that one-third of those who absconded had a similar history in their previous hospitalizations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations